Effects of non-genetic factors on responses to gastro-intestinal nematode infections in Ethiopian sheep - Haile, Aynalem; Tibbo, Markos; Baker, R.L.; Rege, J.E.O. (Springer, 2007)
The effects of non-genetic factors on responses to gastrointestinal nematode infections were examined in artificially infected indigenous Horro and Menz lambs in the central highlands of Ethiopia. The experiment involved lambs of two sexes, infection and monitoring regimens (3 levels), dam parity (4 levels) and birth types (2 levels). A total of 152 weaner lambs (103 Menz and 49 Horro) were used. Endoparasite challenge involved three infection periods (primary, secondary and tertiary) each separated by an anthelmintic treatment. Data were collected on faecal egg counts (FEC), packed cell volume (PCV), worm count, and weight gain. Female lambs were found to harbor lower numbers of T. colubriformis counts and had lower (p < 0.01) FEC in tertiary infection compared to males. Younger animals were more susceptible to the nematode infections than older animals as measured by all the parameters studied (p < 0.01). Twins had higher FEC in both secondary and tertiary infections compared to singles. Lambs born to dams of first parity had higher PCV and lower FEC values during the tertiary infection compared to other parities. These results would be used as basic information in designing a more rational control strategy and should also help to advise on better management care for less resistant sheep.